Urinary laminin‐γ2 is a novel biomarker of non‐muscle invasive urothelial carcinoma. Issue 12 (6th November 2015) - Kamada, Masayuki; Koshikawa, Naohiko; Minegishi, Tomoko; Kawada, Chiaki; Karashima, Takashi; Shuin, Taro; Seiki, Motoharu
Abstract : Lack of appropriate biomarkers has hampered early detection of urothelial cancer (UC), therefore, development of biomarkers for its diagnosis at earlier stages is of importance. Laminin‐332 (Ln‐332, formerly Ln‐5), a component of basement membranes, consists of Ln‐α3, Ln‐β3, and Ln‐γ2 polypeptides. However, monomeric Ln‐γ2 alone is frequently expressed in malignant neoplasms. If Ln‐γ2 is also expressed in UC and secreted into the urine, its detection could be useful for UC diagnosis. Here, we evaluated Ln‐γ2 levels from 60 patients with urinary diseases (including UC) by Western blotting, and detected it in approximately 53% of UC cases. Using immunohistochemistry, we confirmed Ln‐γ2 expression in UC tissues that were positive for Ln‐γ2, whereas Ln‐α3 expression was absent. We next developed a sandwich enzyme‐linked immunosorbent assay and applied it for screening 39 patients with non‐muscle invasive UC and 61 patients with benign urologic diseases. The Ln‐γ2 levels were higher in UC patients than in those with benign urologic diseases. Ln‐γ2 was detected even in patients with earlier stages of UC, such as Ta, T1, or carcinoma in situ . The sensitivity of Ln‐γ2 testing for UC was 97.4%, and the specificity was 45.9%, using a cut‐off of 0.5 μg/g∙crn. Ln‐γ2 had greater diagnostic value for detecting non‐muscle invasive UC compared to conventional urine cytology and available biomarkers for UC, and may be useful as a urine biomarker for the diagnosis and monitoring of UC. Abstract : The sensitivity of Ln‐γ2 testing for urothelial cancer was 97.4%, and the specificity was 45.9%, using a cut‐off of 0.5 pg/mg. Ln‐γ2 may be useful as a urine biomarker for the diagnosis and monitoring of urothelial cancer.